NILAI SOSIAL DALAM CERPEN “NYANYIAN MALAM” KARYA AHMAD TOHARI: PENDEKATAN SOSIOLOGI SASTRA - Siti Karomah; Widowati; Sindy Febrianisa (Universitas Hamzanwadi, 2025)
The purpose of this study is to analyze and describe the social values ​​contained in the short story